Review: Performance Analysis Of Bioelectrochemical System For Domestic Wastewater Treatment In Student Center Building Campus E University Of Sultan Ageng Tirtayasa - Hatifah Bahrum; Fatah Sulaiman; Rahmayetti Rahmayetti (Peneliti.net, 2022)
Bioelectrochemical systems (BES) are an umbrella term for a family of technologies that have evolved from traditional electrochemical systems and in which the electrodic processes are related, either directly or indirectly, to the metabolic activity of particular microorganisms. Despite the fact that BES have not yet reached the commercial scale, these technologies show significant promise because they enable for the valorization of various liquid and gas waste streams. The potential of BES in waste management and valorization is investigated in this chapter. To be more precise, it examines the pragmatics of utilizing BES for energy valorization of wastewaters and CO rich streams. Here, BES is demonstrated to be competitive with standard wastewater treatment methods in terms of energy usage by making use of the energy content of certain compounds found in wastewater. Furthermore, it investigates the potential for BES to allow wastewater treatment plants to be used as a load regulation mechanism for electrical grids. Some of the ways in which BES can help the energy-intensive fertilizers business save money include explaining how it can be used to extract fertilizers from trash. The most important examples of scaling up from the field are discussed as a final section. Performance Analysis, Bio-electrochemical System, Domestic Wastewater Treatment